Aspects of International Law and Human Rights on The Return of The Taliban in Afghanistan - Sofyan Wimbo Agung Pradnyawan; Arief Budiono; Jan Alizea Sybelle (Audito Comparative Law Journal (ACLJ), 2022)
From 1996 to 2001, the Taliban group ruled over Afghanistan before the 2001 World Trade Center bombing in the USA. Then, this group was overthrown by a military invasion that actually served the interests of the North Atlantic Treaty Organization or NATO members. After the absence of strong evidence of the involvement of the Taliban in the 2001 WTC bombing, the United States and its allies began to receive internal and international pressure to immediately withdraw from Afghanistan. This invasion led to the death of many American soldiers. Many survivors suffered from mental disorders. Apart from that, the Afghanistan invasion that went on for 20 years greatly burdened the budget, as its financing reached 31 thousand trillion rupiahs. This study used the normative research method. Results showed that the Taliban's return to power does not violate international law. But in terms of human rights, its return will decrease the human rights index of Afghan citizens. This condition is commonplace in authoritarian countries. This is due to the Taliban’s political attitudes that lack respect for women's rights in the modern era. It also lacks concern for civil rights in a modern democratic state